Comparison of surgical and radiological interventions for thrombosed arteriovenous access. Issue 6 (November 2018) - Lambert, Gary; Freedman, Jonathan; Jaffe, Susan; Wilmink, Teun
Introduction: To compare open surgical and radiological interventions for thrombosed arteriovenous access for dialysis. Methods: A retrospective analysis of access procedures and dialysis episodes from 1 December 2002 to 30 November 2015 with follow-up up to 1 August 2016. Hospital records and dialysis database interrogated for further interventions and length of functional use. Results: Some 128 surgical and 27 radiological thrombectomies were compared. Radiological treatment was successful in 24 (89%) cases and surgical interventions in 65 cases (51%; p < 0.001). In all, 82 (64%) of the 128 surgical thrombectomies had no additional treatment, 43 (34%) had a surgical revision and 3 cases (2%) had an on-table balloon angioplasty. All 27 interventional thrombectomies had an additional balloon angioplasty. Success rate was significantly increased after a surgical revision (74%) or balloon angioplasty (87%) compared to no adjuvant procedure (38%; p < 0.001). There was a trend towards higher primary failure rates of arteriovenous fistula thrombectomies in the upper arm (57%) compared to the arteriovenous fistula thrombectomies in forearm (40%) and arteriovenous graft thrombectomies (33%; p = 0.056). Assisted primary patency was better after interventional treatment compared to surgery (p = 0.02) and significantly better after thrombectomy with additional treatment (p = 0.005). Patency after surgical revision or balloon angioplasty of the access was similar (p = 0.15). More procedures were required to maintain the access after balloon angioplasty than after surgical revision, and intervention-free survival was better after surgical revision (p = 0.02). Conclusion: Revision procedures significantly increase success rate of access thrombectomies. Radiological thrombectomies have higher success rates but lower intervention-free survival and need more additional procedures to maintain patency.